Design of a Compact Broadband 90° Waveguide Twist Based on Double-Corner-Cut Square Slots. (31st December 2017) - Wu, Jun-mo; Zhou, Dong-fang; Lei, Xue; Gao, Jun; Hu, Hao-ming
Abstract : A new compact broadband waveguide twist by double-corner-cut square slots is presented. In particular, the proposed module is made from two substrate layers and three copper cladding layers, which can be used as the waveguide twist and broadband filter. A double-corner-cut square slot is etched on each metal layer with relative rotation. It is found that the optimized module can provide the bandwidths of no less than 6.1% at the 10-dB return-loss level or 4.3% at the 20-dB level with a minimum length of 0.07 waveguide width.